Progress of titanium-based laminated materials by powder metallurgy - XU Jingru; ZHANG Weidong; YANG Peng; CHEN Fulin; WU Zhenggang; CAO Yuankui (Fenmo yejin jishu)
Based on the increasingly severe working environment, properties of titanium materials are facing the new challenges as the superior combination of strength and ductility. The design of laminated structure provides a new idea to achieve the remarkable strength-ductility enhancement of titanium-based materials. In recent years, titanium-based laminated materials have become the research hotspot. Titanium-based laminated materials obtained by different preparation techniques show excellent mechanical properties. Powder metallurgy technology has numerous advantages of simple and efficient process, by which the component control and the optimization of mechanical properties can be easily achieved. The main types and metallurgical processing of titanium-based laminated materials were described in this paper. The research progress of titanium-based laminated materials obtained by powder metallurgy was introduced, and strengthening and toughening mechanism of the high-performance titanium-based laminated structure materials was summarized. Finally, the basic research and practical application of the titanium-based laminated materials were prospected briefly.